A Critique on the Book Nation, State and Rule of Law - Navid Kalahroudi; Ahmad Bostani (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
Javad Tabatabai’s intellectual project has been based on two main axes of the decline of political thought in Iran for the past three decades and in recent decades around the axis of Iranshahri thought. Tabatabai is one of the few writers who has used concepts to explain the history of political thought in Iran within a regular intellectual system, but the scope of his project has caused that not all the themes of Iranshahri political thought have been clearly outlined and studied. This article is an attempt to give a brief description of Tabatabai’s latest work and its important issues such as the position of the First Constitutional Assembly, the concept of tradition, the need to distinguish between nationalism and the Iranian idea, and a reflection on his views, especially on the relationship between his views and issues, contemporary Iran and its criticisms of contemporary intellectuals. The authors argue that although the legacy of ancient Iran is important and significant, without the reconstruction of the classical ideas that are called Iranshahri thought due to Tabatabai's own efforts nowadays, these ideas will remain in a state of ambiguity.